Democratic Republic of the Congo : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Democratic Republic of the Congo. (IMF Staff Country Reports; Country Report ;, 2020)
The Democratic Republic of the Congo is suffering directly from the COVID-19 pandemic with 215 confirmed cases and 20 deaths as of April 9. The economic impact, chiefly through lower commodity prices, was being felt even before the first confirmed case was reported on March 10. The authorities' policy response to the pandemic has been firm, scaling up health care spending and putting in place measures to help contain and mitigate the spread of the disease. The pandemic is also dampening domestic revenue mobilization and putting significant pressures on foreign exchange reserves.